2011
DOI: 10.1038/jid.2010.314
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution of Dermal Resident and Bone Marrow–Derived Cells to Collagen Production during Wound Healing and Fibrogenesis in Mice

Abstract: Recent studies show that bone marrow (BM)-derived cells migrating into a dermal wound promote healing by producing collagen type I. However, their contribution to the repair process has not been fully verified yet. It is also unclear whether BM-derived cells participate in dermal fibrogenesis. We have addressed these issues using transgenic mice that harbor tissue-specific enhancer/promoter sequences of α2(I) collagen gene linked to either enhanced green fluorescent protein (COL/EGFP) or the luciferase (COL/LU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 34 publications
4
58
0
Order By: Relevance
“…There is a controversy on whether or not fibrocytes participate in skin wound repair. A few experiments revealed that no fibrocyte was detected during skin wound healing (Barisic-Dujmovic et al, 2010;Higashiyama et al, 2011). However, many others certified the recruitment of fibrocytes after skin injury (Ishii et al, 2005;Mori et al, 2005;Ou et al, 2015;Suga et al, 2014).…”
Section: Cb 2 Receptor Activation Attenuates Fibrogenesismentioning
confidence: 95%
“…There is a controversy on whether or not fibrocytes participate in skin wound repair. A few experiments revealed that no fibrocyte was detected during skin wound healing (Barisic-Dujmovic et al, 2010;Higashiyama et al, 2011). However, many others certified the recruitment of fibrocytes after skin injury (Ishii et al, 2005;Mori et al, 2005;Ou et al, 2015;Suga et al, 2014).…”
Section: Cb 2 Receptor Activation Attenuates Fibrogenesismentioning
confidence: 95%
“…It is generally accepted that the major source of myofibroblasts are local connective tissue fibroblasts that are recruited into the wound 30. Dermal fibroblasts located at the edges of the wound can acquire a myofibroblastic phenotype and participate in tissue repair 31.…”
Section: Origin Of Wound Myofibroblastsmentioning
confidence: 99%
“…This population of fibroblasts have the capacity to differentiate into multiple lineages (23) and have been termed mesenchymal stem or stromal cells (MSCs). Initial reports suggested that MSCs can contribute to the dermis (24)(25)(26), but subsequent studies do not appear to support this finding (27)(28)(29). Interestingly, clinical trials have suggested that the infusion of MSCs into the blood may ameliorate several diseases, such as graft-versus-host disease (30,31).…”
Section: Introductionmentioning
confidence: 99%